SAMRAT ASHOKAS INSCRIPTIONS AND AYURVEDA: A REVIEW (International Journal of Ayurveda and Pharma Research, 2019)
Samrat Ashoka was the grandson of Chandragupta and he founded the Mauryan dynasty empire about 324 B.C. Ashoka built a large number of inscriptions on rocks and pillars to propagate Buddhist message of loving kindness. He was the follower of Buddhist thought after Kalinga war. He had dug wells and planted trees and medicinal plants along the roads for human beings as well as animals. The fundamental principles of Ayurveda have been based on Indian philosophical sciences such as Aastika and Nastika Darshan. Ancient Indian history has been written mainly based on texts/literatures but there was some role of coins sand inscriptions also. The total number of incretions inscribed on rocks, pillars, caves by Samrat Ashoka has reached 42 but in this article only two (Girnar’s second and Dhauli’s first Shilalekh) which is related to Ayurveda has been reviewed.